Cuidados paliativos na formação médica: relato de experiência e revisão de literatura - Hernández, Carla Vitória Pedroso (Universidade Federal de São Carlos, 2024)
In recent decades, following the global trend, population censuses have shown an increase in life expectancy in Brazil (BIVAR; ABRANTES, 2014). This increase is tied to the growing representation of the elderly population, with projections indicating that by 2050, the age group over 65 years will account for 22.77% of the total population in the country (UNITED NATIONS, 2015). However, the increase in years lived does not necessarily represent years lived free of disease. Thus, there has been an increase in chronic non-transmissible diseases in the population (BRASIL, 2021). In this scenario, the incorporation of palliative care into routine healthcare becomes undeniable, with the undergraduate environment being a key setting to consolidate concepts on the subject, which are essential for future medical practice. Nevertheless, medical education still seems to lack a more structured and standardized approach to learning on this topic. The present work aims to explore the experiences lived by the student during undergraduate studies, focusing on the theme of palliative care. It also aims to conduct a narrative literature review regarding the relevance of this type of care in the current and future epidemiological context, as well as to discuss how the teaching of this topic is currently being approached in undergraduate programs, primarily from the perspective of students. This is an experience report, with a bibliographic complement using national and international databases. It is concluded that the recent update of the National Curriculum Guidelines for Undergraduate Medicine Programs, conducted by the Ministry of Education in Brazil, may enhance the landscape of medical education from the perspective of palliative care in the coming years. For this to become a reality, it is essential to modify the medical curriculum of institutions that do not yet include the discussion of this topic in a more standardized way, incorporating practical learning with structured assessment, tailored to the particularities of each educational project.
Palliative care in medical training: experience report and review of literature
Keywords: Cuidados paliativos; Formação médica; Educação médica; Relação médico paciente; CIENCIAS DA SAUDE::MEDICINA